Keanekaragaman Serangga pada Tanaman Jambu Biji (Psidium gujava L) di Desa Serbajadi Kecamatan Sunggal Kabupaten Deli Serdang - Ibnu Hasyim Lubis; Kartika Manalu; Efrida Pima Sari Tambunan (Program Studi Pendidikan Biologi, 2022)
The purpose of this study was to classify whether the insects present in the Guava (Psidium guajava L.) plant at the time of fruiting and flowering in Serba Jadi Village, Sunggal District, Deli Serdang Regency, were insect pests, pollinators or just visitors. Sampling was carried out in Serbajadi Village, Sunggal District, Deli Serdang Regency, Sampling, namely by catching insects that perched on guava fruit and flowers (Psidium guajava L) using insect nets (sweep net) and then put them in film bottles. Identification of the caught insects using the book Key Determination of Insects Donald J Borror 1992. The types of insects found on guava (Psidium gujava L) on fruit and flowers in Serbajadi Village, Sunggal District, Deli Serdang Regency are Oxyafusco vittata, Oxyachinensis, Xylocopa aestuans, Orthetrumsabina, Agriocnemis splendidissima, Pelopidas mathias, Bactrocera dorsalis and Drosophila melanogaster.